2015
DOI: 10.1017/s1751731115000488
|View full text |Cite
|
Sign up to set email alerts
|

Determination of protein and amino acid requirements of lactating sows using a population-based factorial approach

Abstract: Determination of appropriate nutritional requirements is essential to optimize the productivity and longevity of lactating sows. The current recommendations for requirements do not consider the large variation between animals. Therefore, the aim of this study was to determine the amino acid recommendations for lactating sows using a stochastic modeling approach that integrates population variation and uncertainty of key parameters into establishing nutritional recommendations for lactating sows. The requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
11
2
Order By: Relevance
“…Based on the average feed intake and the SID CP concentration of 135 g/kg (Strathe et al, 2017a), the daily requirement for optimal litter ADG was estimated to be 850 g SID CP/day. The 850 g SID CP/day found in the current study was considerably higher than the 700 g SID CP/day estimated in the NRC model (National Research Council, 2012) and slightly lower than the 880 g SID CP/day (±70 g/day) estimated in the requirement model by Strathe et al (2015). The largest difference between the two models is the equation used to determine milk production: the one used by NRC (2012) is based on weigh-suckle-weigh data, which underestimates milk yield and thereby estimates a lower requirement (Hansen et al, 2012).…”
Section: Discussioncontrasting
confidence: 84%
“…Based on the average feed intake and the SID CP concentration of 135 g/kg (Strathe et al, 2017a), the daily requirement for optimal litter ADG was estimated to be 850 g SID CP/day. The 850 g SID CP/day found in the current study was considerably higher than the 700 g SID CP/day estimated in the NRC model (National Research Council, 2012) and slightly lower than the 880 g SID CP/day (±70 g/day) estimated in the requirement model by Strathe et al (2015). The largest difference between the two models is the equation used to determine milk production: the one used by NRC (2012) is based on weigh-suckle-weigh data, which underestimates milk yield and thereby estimates a lower requirement (Hansen et al, 2012).…”
Section: Discussioncontrasting
confidence: 84%
“…The ADFI in individual weeks of lactation also had a positive correlation to the ADG of the litter, especially in weeks 3 and 4 even though the effect of the total ADFI for the entire lactation period was more pronounced. This makes sense because around days 16 to 18 postpartum the sows reach their maximum milk production and therefore has the highest energy and nutrient requirement (Strathe et al, 2015); Koketsu et al, (1997) also investigated the effect of ADFI in individual weeks of lactation on litter weight at weaning; and similarly found that ADFI of weeks 2 and 3 had a higher impact than ADFI in week 1. It is nevertheless important to mention that the sows in the current study did not have ad libitum access to feed, but an upper limit was set on the feed allowance.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies evaluating the effects of arginine supplementation for gestating sows on the intrauterine development of the litter have conflicting results (Li et al., ; Novak et al., ; Quesnel et al., ). It is known that, in addition to dietary levels of arginine, lysine, and protein (Li et al., ), gestational age for supplementation (Li et al., ), the parity of the sow (Li et al., ), the litter size (Strathe, Strathe, Theil, Hansen, & Kebreab, ), and environmental conditions (Laspiur & Trottier, ) may also influence the results. To date, there is no consensus about the best way to use this amino acid in diets of gestating sows.…”
Section: Introductionmentioning
confidence: 99%